Different Relationship Between Systolic Blood Pressure and Cerebral Perfusion in Subjects With and Without Hypertension. Issue 1 (January 2019) - Glodzik, Lidia; Rusinek, Henry; Tsui, Wai; Pirraglia, Elizabeth; Kim, Hee-Jin; Deshpande, Anup; Li, Yi; Storey, Pippa; Randall, Catherine; Chen, Jingyun; Osorio, Ricardo S.; Butler, Tracy; et al.
Abstract : Although there is an increasing agreement that hypertension is associated with cerebrovascular compromise, relationships between blood pressure (BP) and cerebral blood flow are not fully understood. It is not known what BP level, and consequently what therapeutic goal, is optimal for brain perfusion. Moreover, there is limited data on how BP affects hippocampal perfusion, a structure critically involved in memory. We conducted a cross-sectional (n=445) and longitudinal (n=185) study of adults and elderly without dementia or clinically apparent stroke, who underwent clinical examination and brain perfusion assessment (age 69.2±7.5 years, 62% women, 45% hypertensive). Linear models were used to test baseline BP-blood flow relationship and to examine how changes in BP influence changes in perfusion. In the entire group, systolic BP (SBP) was negatively related to cortical (β=−0.13, P =0.005) and hippocampal blood flow (β=-0.12, P =0.01). Notably, this negative relationship was apparent already in subjects without hypertension. Hypertensive subjects showed a quadratic relationship between SBP and hippocampal blood flow (β=−1.55, P =0.03): Perfusion was the highest in subjects with mid-range SBP around 125 mm Hg. Longitudinally, in hypertensive subjects perfusion increased with increased SBP at low baseline SBP but increased with decreased SBP at high baseline SBP. Cortical and hippocampal perfusion decrease with increasing SBP across the entire BP spectrum. However, in hypertension, there seems to be a window of mid-range SBP which maximizes perfusion. Abstract : Supplemental Digital Content is available in the text.